2017
DOI: 10.1039/c7cp04612j
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the energy storage behaviour of layered α-V2O5 as a pseudo-capacitive electrode using operando Raman spectroscopy and a quartz crystal microbalance

Abstract: α-VO nanowires with a layered structure have been fabricated through a two-step procedure. When measured as a pseudo-capacitive electrode with a three-electrode configuration in 1 M NaSO aqueous solutions, α-VO exhibits ideal capacitive characteristics with a specific capacitance of ∼238 F g at a high current of 2 A g, but poor cycling stability with a continuous drop in the first 2000 cycles before it is maintained. To find possible solutions towards this problem, the energy storage behavior of the α-VO elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…Such an effect was expected due to the differences of flat-band potential of two photoanode materials [37]. The curve of V 2 O 5 consists also a dark current anodic hump at 0.2-0.6 V. It was previously reported that at this range of applied potential, electrochemical oxidation with simultaneous Na + desorption occurs, what was confirmed using electrochemical quartz crystal microbalance and in situ Raman spectroscopy [38]. This phenomenon should be rather confined to the surface or a few crystallographic planes of the studied thin film than to the bulk oxide because current response is recorded at relatively high sweep rates.…”
Section: Photoelectrochemical Performancesupporting
confidence: 55%
“…Such an effect was expected due to the differences of flat-band potential of two photoanode materials [37]. The curve of V 2 O 5 consists also a dark current anodic hump at 0.2-0.6 V. It was previously reported that at this range of applied potential, electrochemical oxidation with simultaneous Na + desorption occurs, what was confirmed using electrochemical quartz crystal microbalance and in situ Raman spectroscopy [38]. This phenomenon should be rather confined to the surface or a few crystallographic planes of the studied thin film than to the bulk oxide because current response is recorded at relatively high sweep rates.…”
Section: Photoelectrochemical Performancesupporting
confidence: 55%
“…[ 43,237 ] Electrode dissolution in aqueous solution will limit the long‐term cyclability and cause secondary pollution to the outlet water. The dissolution of electrode materials in aqueous solution has been noted in previous electrochemical reports, [ 42,165,169,341–343 ] such as disproportionation of Mn 3+ ‐containing manganese oxides to Mn 2+ and Mn 4+ , [ 165,169 ] the general instability of metal hexacyanometalates at pH 7, [ 342 ] and the high solubility of silver of 8.9 ppm in 600 × 10 −3 m NaCl solution. [ 42 ] Nevertheless, due to the CDI being in its infancy stage, current studies are still focused on the feasibility of various emerging Faradiac electrode materials but lack effective strategies to address the aforementioned issues.…”
Section: Summary and Perspectivesmentioning
confidence: 96%
“…[24] When charging the Mn 3 O 4 electrode from 0 to 1.2 V versus Ag/AgCl, the Mn valence state was stable in the potential range of 0-0.75 V, but increased in the potential range of 0.75-1.2 V. This discontinuous valence change was different from the continuous change in MnO 2 discussed above, and can be related to redox reactions occurring at high potentials. [27] Structural changes of α-V 2 O 5 during charge-discharge cycling revealed that no phase changes occurred and that VOV and VO bond lengths were changed. The charge storage mechanisms of the Mn 3 O 4 electrodes were also detailed by operando Raman spectroscopy [25] and, contrarily to the previous report, an irreversible transformation from Mn 3 O 4 to MnO 2 phase and Na + and Mn 2+ (extracted from tetrahedral sites) intercalation into the defects or tunnel sites of the MnO 2 in the first charge were noticed (Equation (8) [26] The charging was related to K + deintercalation from (001) interlayers, which weakened the interaction of K + with negatively charged [VO 6 ] octahedra, leading to expansion of (001) interlayers.…”
Section: Mn Oxidesmentioning
confidence: 99%